MiR-449a antagonizes EMT through IL-6-mediated trans-signaling in laryngeal squamous cancer - Alessia Maria Cossu; Federica Melisi; Teresa Maria Rosaria Noviello; Lucia Stefania Pasquale; Piera Grisolia; Carla Reale; Marco Bocchetti; Michela Falco; Chiara Tammaro; Nunzio Accardo; Francesco Longo; Salvatore Allosso; et al. (Elsevier, 2024)
MicroRNAs (miRNAs) are involved in post-transcriptional gene expression regulation and in mechanisms of cancer growth and metastases. In this light, miRNAs could be promising therapeutic targets and biomarkers in clinical practice. Therefore, we investigated if specific miRNAs and their target genes contribute to laryngeal squamous cell carcinoma (LSCC) development. We found a significant decrease of miR-449a in LSCC patients with nodal metastases (63.3%) compared with patients without nodal involvement (44%). The AmpliSeq Transcriptome of HNO-210 miR-449a-transfected cell lines allowed the identification of IL6-R as a potential target. Moreover, the downregulation of IL6-R and the phosphorylation reduction of the downstream signaling effectors, suggested the inhibition of the IL-6 trans-signaling pathway. These biochemical effects were paralleled by a significant inhibition of invasion and migration in vitro and in vivo, supporting an involvement of epithelial-mesenchymal transition. These findings indicate that miR-449a contributes to suppress the metastasization of LSCC by the IL-6 trans-signaling block and affects sensitivity to external stimuli that mimic pro-inflammatory conditions.